A New Historiography of the Origins of the Cold War - Adewunmi James Falode (Politeknik Negeri Bali, 2019)
The Cold War that occurred between 1945 and 1991 was both an international political and historical event. As a political event, the Cold War laid bare the fissures, animosities, mistrusts, misconceptions and the high-stake brinksmanship that has been part of the international political system since the birth of the modern nation-state in 1648. As a historical event, the Cold War and its end marked an important epoch in human social, economic and political development. The beginning of the Cold War marked the introduction of a new form of social and political experiment in human relations with the international arena as its laboratory. Its end signaled the end of a potent social and political force that is still shaping the course of political relationship among states in the 21st century. The historiography of the Cold War has been shrouded in controversy. Different factors has been advanced as being responsible for the origins of the conflict. This work is a historical and structural analysis of the historiography of the Cold War. The work attempts to synthesize the competing views of the origins of the Cold War and create an all-encompassing and holistic historiography for its origins.